2012
DOI: 10.1177/147323001204000413
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Paraspinal Approach with a Percutaneous Approach in the Treatment of Thoracolumbar Burst Fractures with Posterior Ligamentous Complex Injury: A Prospective Randomized Controlled Trial

Abstract: The minimally invasive percutaneous approach appears to be better in cases of successful postural reduction. The paraspinal approach results in better surgical correction and is, therefore, recommended for patients without successful postural reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 33 publications
5
72
0
1
Order By: Relevance
“…After more than 3 years, the authors concluded that the paraspinal approach is able to correct deformity in the case of unsuccessful postural reduction, but there were no significant differences between groups in long-term stability. 6 Radiological data in our study did not deviate from previously published patient series. We found significant correction in all monitored parameters in both groups, and the percutaneous technique was even slightly better compared with the control group in terms of restoration of VBI.…”
Section: Discussionsupporting
confidence: 57%
“…After more than 3 years, the authors concluded that the paraspinal approach is able to correct deformity in the case of unsuccessful postural reduction, but there were no significant differences between groups in long-term stability. 6 Radiological data in our study did not deviate from previously published patient series. We found significant correction in all monitored parameters in both groups, and the percutaneous technique was even slightly better compared with the control group in terms of restoration of VBI.…”
Section: Discussionsupporting
confidence: 57%
“…Since Assaker [21] first reported on the application of percutaneous pedicle screw fixation in thoracolumbar trauma, many studies [17,[22][23][24][25][26] were conducted to compare the percutaneous pedicle screw fixation technique with the conventional open approach, which showed that the clinical, functional, and radiological outcomes of the minimally invasive technique were the same as those achieved using the open technique, with a significant reduction in blood loss, post-operative pain, and surgical time. A systematic review and meta-analysis of comparative studies [27] on the percutaneous versus open pedicle screw fixation for treatment of thoracolumbar fractures showed that there was no difference in efficacy between percutaneous versus open pedicle screw fixation techniques, but the percutaneous approach was associated with shorter surgical time and hospital stay, less intraoperative blood loss and infection rate.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous pedicle screw fixation systems were originally in the realm of degenerative spinal disease, and have been shown to be effective in avoiding tissue and muscle disruption, whilst shortening hospital and recovery duration, reducing blood loss and complications [17,18]. Whilst similar advantages have also been shown for treatment of thoracolumbar fractures in some reports, the evidence is mainly limited to low-grade, inadequately powered observational studies [3,14,27,31]. Furthermore, long-term outcomes of percutaneous pedicle screw fixation for thoracolumbar fractures has not been well established, further limiting the evidence available for this technology.…”
Section: Introductionmentioning
confidence: 99%